A Nutrition-Related Factor-Based Risk Stratification for Exploring the Clinical Benefits in the Treatment of Patients With Locally Advanced Esophageal Squamous Cell Carcinoma Receiving Definitive Chemoradiotherapy: A Retrospective Cohort Study - Yu, Yilin; Wu, Haishan; Qiu, Jianjian; Ke, Dongmei; Wu, Yahua; Lin, Mingqiang; Liu, Tianxiu; Zheng, Qunhao; Zheng, Hongying; Yang, Jun; Wang, Zhiping; Li, Hui; et al. (Frontiers in Nutrition, 2022)
Objective: No study has reported the risk stratification of BMI and PNI in patients with locally advanced esophageal squamous cell carcinoma (ESCC) undergoing definitive chemoradiotherapy (dCRT). This study aimed to construct a risk stratification to guide the treatment of ESCC following dCRT. Methods: A total of 1068 patients with locally advanced ESCC who received dCRT were retrospectively analyzed. The impacts of clinicopathological factors on overall survival (OS) and progression-free survival (PFS) were analyzed. Besides, the novel prognostic indices of pre-therapeutic nutritional index (PTNI) and prognostic index (PI) were developed. Results: The median follow-up period of OS and PFS were 22.9 and 17.4 months, respectively. The high body mass index (BMI) group had better 5-year OS and PFS (36.4% and 34.0%) than the low BMI group (18.8% and 17.2%). The high prognostic nutritional index (PNI) group also had better 5-year OS and PFS (33.4% and 30.9%) than the low PNI group (17.5% and 17.2%). Multivariate Cox regression analysis showed that BMI and PNI were independent prognostic factors for OS and PFS. Based on nutritional indices, patients were categorized into the low-risk ( PTNI = 1), medium-risk (PTNI = 2), and high-risk (PTNI = 3) groups with 5-year OS rates of 38.5%, 18.9%, 17.5%, respectively (p < 0.001) and 5- year PFS rates of 35.8%, 17.6%, 16.8%, respectively (p < 0.001). Besides, we also constructed a prognostic index (PI) for OS and PFS which was calculated based on statistically significant factors for predicting OS and PFS. The results revealed that the high-risk group had worse OS and PFS than the low-risk group (p < 0.001). Finally, RCS analysis demonstrated a nonlinear relationship between the PNI, BMI, and survival for patients with ESCC. The death hazard of PNI and BMI sharply decreased at 41.8 and 19.7. Conclusions: The decreased pre-therapeutic BMI and PNI levels were associated with a worse survival outcome. BMI and PNI are readily available and can be used to stratify risk factors for locally advanced ESCC patients undergoing dCRT. The novel risk stratification may help to evaluate patients’ pre-therapeutic status and guide dCRT for locally advanced ESCC patients.